INDONESIAN PRESIDENCY AT THE G20 FORUM - Harun Umar; Irma Indrayani (Journal of Social Political Sciences, 2022)
This paper analyses the Indonesian Presidency at the G20 forum. The question is how Indonesia can hold a meeting in a situation where member countries conflict due to Russia's invasion of Ukraine. In addition, the tug-of-war interests of major G20 member countries. Nevertheless, the G20 Presidency reaffirmed Indonesia's leadership in diplomacy and economy in the region as the only ASEAN country member of the G20. In addition, it is also a building image of Indonesia's economic resilience to its main crisis during the Covid-19 pandemic. This research uses the perspective of international political economy because of the influence of politics on meetings that are purely economic forums. The qualitative approach in this study focuses on analysis based on a series of meetings starting from Working Groups, Ministerial Meetings until later in November 2022. The Indonesian government mobilized all track diplomacy starting from track 1, G to G countries, and public diplomacy to the city level to succeed in the G20 Summit in Bali. The conclusion found that the interrelationship between the economic and political fields cannot be separated in implementing a country’s diplomacy in bilateral and multilateral relations.